2004
DOI: 10.1124/dmd.32.6.620
|View full text |Cite
|
Sign up to set email alerts
|

RAT AND MOUSE DIFFERENCES IN GENDER-PREDOMINANT EXPRESSION OF ORGANIC ANION TRANSPORTER (OAT1–3;SLC22A6–8) mRNA LEVELS

Abstract: ABSTRACT:Organic anion transporters (Oats) mediate the initial step of active renal excretion, specifically substrate uptake into proximal tubule cells. Despite extensive characterization of rat Oats, mouse Oat expression patterns are virtually unknown. This study was designed to identify basal expression patterns of mouse Oat1 (Slc22a6), Oat2 (Slc22a7), and Oat3 (Slc22a8) mRNA, compare these patterns with those in rat, and characterize postnatal development of mouse Oat mRNA. Tissues were collected from adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
112
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 22 publications
(33 reference statements)
16
112
2
Order By: Relevance
“…In such a case, it will be of interest to determine the mechanism supporting this organ-specific gender-dependent regulation. As alluded to above, renal Oat2 mRNA and protein was reported to be predominant in female rats and mice [56,[124][125][126][127]. Castration of male rats markedly increased renal rOat2 mRNA and protein [126,127], whereas ovariectomy in females resulted in a relatively weak reduction in rOat2 mRNA and protein [126].…”
Section: Gender and Specific Sex Hormonesmentioning
confidence: 90%
See 4 more Smart Citations
“…In such a case, it will be of interest to determine the mechanism supporting this organ-specific gender-dependent regulation. As alluded to above, renal Oat2 mRNA and protein was reported to be predominant in female rats and mice [56,[124][125][126][127]. Castration of male rats markedly increased renal rOat2 mRNA and protein [126,127], whereas ovariectomy in females resulted in a relatively weak reduction in rOat2 mRNA and protein [126].…”
Section: Gender and Specific Sex Hormonesmentioning
confidence: 90%
“…In the first assessment, it was found that renal rOat1 mRNA levels were not different between male and female rats [124]. However, in several subsequent reports, male rats and mice exhibited higher mRNA levels [55,56,125]. Furthermore, a reduction in rOat1 mRNA via gonadectomy in males confirmed that this difference was due to greater androgen levels in males [125].…”
Section: Gender and Specific Sex Hormonesmentioning
confidence: 90%
See 3 more Smart Citations